2020
DOI: 10.31234/osf.io/4jcf7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual differences in epistemically suspect beliefs: The role of analytic thinking and susceptibility to cognitive biases

Abstract: The endorsement of epistemically suspect beliefs (i.e. paranormal, conspiracy, and pseudoscientific beliefs) is both surprisingly widespread and has been shown to have important negative real-life consequences. For these reasons, it is important to understand individual differences in epistemically suspect beliefs and their associations with other cognitive phenomena, such as biases in reasoning and decision-making domain. In the present study (N = 397), I examined the relationship between five reasoning biase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
(123 reference statements)
0
23
0
Order By: Relevance
“…Multiple findings consistently showed that it is a robust negative predictor of unfounded beliefs. Namely, CR was predictive of lower endorsement of paranormal, superstitious, pseudoscientific and conspiracy beliefs (Pennycook, Cheyne, Seli, Koehler, & Fugelsang, 2012;Pennycook, Cheyne, Koehler, & Fugelsang, 2019;Pennycook, Fugelsang, & Koehler, 2015;Ståhl & Van Prooijen, 2018;Šrol, 2020) and higher endorsement of scientifically founded beliefs (McPhetres & Pennycook, 2019;Pennycook et al, 2019). Recently, Pennycook, McPhetres, Zhang and Rand, (2020) found that these findings also extend to beliefs about C-19.…”
Section: Introductionmentioning
confidence: 94%
“…Multiple findings consistently showed that it is a robust negative predictor of unfounded beliefs. Namely, CR was predictive of lower endorsement of paranormal, superstitious, pseudoscientific and conspiracy beliefs (Pennycook, Cheyne, Seli, Koehler, & Fugelsang, 2012;Pennycook, Cheyne, Koehler, & Fugelsang, 2019;Pennycook, Fugelsang, & Koehler, 2015;Ståhl & Van Prooijen, 2018;Šrol, 2020) and higher endorsement of scientifically founded beliefs (McPhetres & Pennycook, 2019;Pennycook et al, 2019). Recently, Pennycook, McPhetres, Zhang and Rand, (2020) found that these findings also extend to beliefs about C-19.…”
Section: Introductionmentioning
confidence: 94%
“…Cognitive biases, as systematic departures from what is normatively defined rational behavior, can be viewed as yet another broad category of irrational beliefs. Although they have been proven to be predictive of some paranormal (Bressan, 2002;Pennycook et al, 2012;Šrol, 2020;van Prooijen et al, 2017) and pseudoscientific beliefs (Pennycook, Cheyne et al, 2015;Redelmeier & Tversky, 1996;Šrol, 2020), cognitive biases remain underexplored in the domain of both PSPs and adherence to public health guidelines. The list of cognitive biases is considerably heterogeneous and ever evolving (Kahneman & Frederick, 2005;Pohl, 2004;Stanovich, 2009;Teovanović et al, 2015).…”
Section: Practices During the Covid-19 Pandemicmentioning
confidence: 99%
“…In our study, biases that are based on making a type I error were represented by the illusory correlation detection (Smedslund, 1963), base‐rate neglect (Tversky & Kahneman, 1974), gambler's fallacy (Tversky & Kahneman, 1974), and hot‐hand fallacy (Gilovich et al, 1985) bias. Although cognitive biases have shown to be predictive of some paranormal (Bressan, 2002; Pennycook et al, 2012; Šrol, 2020; van Prooijen et al, 2017) and pseudoscientific beliefs (Pennycook, Cheyne, et al, 2015; Redelmeier & Tversky, 1996; Šrol, 2020), they remain underexplored in the domain of both PSPs and adherence to public health guidelines. Starting from the general hypothesis about relation between irrational beliefs and health behaviors, we expected that a higher susceptibility to such cognitive biases would predict lesser adherence to COVID‐19 guidelines (H3a), greater use of PSPs (H3b), and weaker intention to get vaccinated (H3c).…”
mentioning
confidence: 99%
“…Multiple findings consistently showed that it is a robust negative predictor of unfounded beliefs. Namely, cognitive reflection was predictive of lower endorsement of paranormal, superstitious, pseudoscientific and conspiracy beliefs (Pennycook et al 2012;Pennycook et al in press, 2015;Ståhl and Van Prooijen 2018;Šrol 2020) and higher endorsement of scientifically founded beliefs (McPhetres and Pennycook 2019;Pennycook et al in press). Several recent studies (e.g.…”
Section: Introductionmentioning
confidence: 97%